Elimination of volatile organic compounds in paint drying by absorption reaction in water combined with the ozone oxidation technique - Alvarez, Juan Martín (2020)
The aim of this work was to evaluate the treatment of Volatile Organic Compounds (VOCs) released during the painting and drying process of an industrial paint by absorbing them in a water curtain and then oxidizing them with ozone. For this purpose, laboratory equipment was built consisting of a paint drying cabin and a bubble column where the VOCs were absorbed and treated. Tests were carried out with simulated effluents using distilled water and service water, to which 3.5 μg/L of formaldehyde, 11.6 mg/L of butyl acetate, 5.3 mg/L of ethanol and 5.6 mg/L of methyl ethyl ketone were added, according to data provided by the paint manufacturer; these tests were then repeated using the industrial paint currently used in the processes. The water saturation with the VOCs and the simultaneous treatment by means of ozone dosage was studied, taking the Chemical Oxygen Demand (COD) value as a treatment effectiveness parameter. VOC saturation is achieved for exposure times between 5-15 minutes in the aqueous effluent. The system of absorption and ozonation is effective for the elimination of the released VOCs, achieving a 94% reduction in the COD of the wastewater. Finally, it was observed that when O3 is injected together with the paint, the reduction of COD in the effluent is favored due to a first instance of direct ozonation of the VOCs, and a second, slower indirect stage, generated by the presence of free radicals from the reaction of O3 with water [hydroxyl radical (HO?), superoxide anion radical (O2??) and hydroperoxyl radical (HO2?)] favored by the pH of the solution. The reaction kinetics of VOC oxidation is of first order.